2014
DOI: 10.2135/cropsci2013.08.0513
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Soybean Germplasm Accessions for Resistance to Phakopsora pachyrhizi Populations in the Southeastern United States, 2009–2012

Abstract: Between 2009 and 2012, 118 soybean [Glycine max (L.) Merr.] accessions from the USDA Soybean Germplasm Collection were screened for resistance to soybean rust (Phakopsora pachyrhizi) at up to five locations in the southeastern United States. In 2009, plant introductions (PIs) from maturity groups III through IX were evaluated for relative disease severity and intensity of sporulation from uredinia compared with 12 susceptible cultivars from the same range of maturity groups. Resistance evaluations were based p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(60 citation statements)
references
References 53 publications
2
57
1
Order By: Relevance
“…The wide variation in the type of reaction, color and intensity of sporulation observed in the field can be a difficulty factor in genotype characterization studies [53]. Although the type of lesions are widely used in detached leaves and seedlings inoculations studies, the appearance of rust lesions in adult plants is often different from that originally reported by Bromfield & Hartwig [17].…”
Section: Resistancementioning
confidence: 98%
See 1 more Smart Citation
“…The wide variation in the type of reaction, color and intensity of sporulation observed in the field can be a difficulty factor in genotype characterization studies [53]. Although the type of lesions are widely used in detached leaves and seedlings inoculations studies, the appearance of rust lesions in adult plants is often different from that originally reported by Bromfield & Hartwig [17].…”
Section: Resistancementioning
confidence: 98%
“…Walker et al [53], studying the field reaction of reported resistance genes in the southern United States, noted that Rpp1 gene, present in PI 200492, and Rpp6 gene, in PI 567102B, still conferred high levels of resistance. The varieties carrying Rpp2, Rpp3, Rpp4 or Rpp5 showed incomplete resistance and moderate levels of rust development when compared to susceptible controls.…”
Section: Resistancementioning
confidence: 99%
“…In addition to being an important initial source for urediniospores, kudzu could also be a source of selection pressure for the pathogen population. For example, inoculum prepared from infected kudzu leaves collected in northcentral Florida in 2012 caused unusually high levels of soybean rust on a number of historically resistant soybean germplasm accessions (Walker et al 2014a). …”
Section: Epidemiologymentioning
confidence: 99%
“…Multiple resistance gene alleles have been mapped to the Rpp1, Rpp3, and Rpp5 loci Hossain et al 2015), and some alleles that condition a high level of resistance to fungal populations and isolates from one continent are entirely ineffective against those from another (Walker et al 2014b). The Rpp6 gene is unusual in that it has provided a high level of resistance to numerous field populations and isolates from North and South America (Li et al 2012;Miles et al 2008;Walker et al 2011Walker et al , 2014a, though some populations or isolates have been able to overcome Rpp6-based resistance (Paul et al 2013;Walker et al 2014b). In addition, Japanese 'Hyuuga' soybean was found to have two resistance genes at the Rpp3 and Rpp5 loci (Kendrick et al 2011).…”
Section: Soybean Rust Managementmentioning
confidence: 99%
See 1 more Smart Citation